Ethnobotanical and agronomical survey of Brocchia cinerea (Delile) Vis. plant used by people in the Figuig and Draa-Tafilalet regions, Morocco - Nisrine Chlif; Mohammed Diouri; Noureddine El Messaoudi; Aissam Sbai; Amar Bentayeb (GarVal Editorial Ltda., 2021)
Context: As part of the development of the natural heritage of Morocco, an ethnobotanical and agronomic study was conducted in the regions of Figuig and Draa- Tafilalet. Aims: To collect detailed information about the usage of Brocchia cinerea plant in human therapy and its incorporation into the feed system of livestock. Methods: The survey was carried out over five months, using semi-structured and structured interviews. A total of 197 interviews with traditional health practitioners and educated villagers were conducted. Results: Interview results showed that Brocchia cinerea is used in indigenous pharmacopeia to alleviate common diseases symptoms of the digestive system (36%), nervous system (19%), respiratory system (17%), ear, nose and throat (ENT) disorders (8%), and rheumatism (7%). The aerial parts of this plant were the most commonly used (36%), and the most preferred method for the preparation of traditional drugs was a decoction (33%). The results obtained from the agronomical survey show that the milk yield and meat production in ruminants noticeably increase after consumption of this plant. Conclusions: The data collected may help prevent the loss of traditional knowledge on the use of plants characterizing the ecosystem of these study areas and may constitute preliminary information required for a future phytochemical study on the plants most frequently used. The agronomic survey carried out can help the range managers improve the forage quality by using Brocchia cinerea for the betterment of animal health and productivity.